Teoria da sensibilidade e a relação entre sentimento e valor - Adelino Ferreira (2017)
The relationship between sentiment and value is a subject of great discussion in metaethics. Among the various positions available in the debate, this dissertation deals specifically with the so-called Sensibility Theory, a realistic thesis on moral discourse that supports the non-priority character between sentiments and moral properties. According to such a conception, the phenomenology of values can be understood analogously to the phenomenology of secondary qualities, like colors. Such similarity, however, although it is an attractive point of the theory, must always be thought of as an analogy, that is, something that holds some important distinctions. In order to analyze the main arguments and limits of the Sensibility Theory, we will discuss, in particular, John McDowell texts on the subject. At first, in the debate on moral language, the theory will be confronted with classical non-cognitivist and cognitivist alternatives to make explicit the distinctive character of McDowell's proposal not to commit himself explicitly to any extreme of the debate. In a second, we will analyze the phenomenology of the secondary qualities - presenting and discussing the existing theories in the literature - and the points of similarity and difference of the phenomenology of values. We will also explain the irreducible and autonomous character of morality in relation to other domains. Finally, we will deal with a fundamental question for proposals such as the Sensibility Theory, that is, the explanation of the criteria of correction for moral judgments. One possible answer concerns the resumption of some elements of Aristotelian reflections on morality, and especially on the role of virtue, by McDowell.